Uso de nuevas tecnologías para mejorar el rendimiento del cultivo de arroz en la zona de Los Ríos. - Peña Arias, Renzo Rubén (2022)
In the present work a complete study on the implementation of new technologies that help to improve the yield of rice cultivation specifically in the province of Los Rios, classified information was obtained where the benefits for the rice farmer of this province are demonstrated, achieving in this way to compare the traditional crop and using specialized machinery that include within the technology. The methods of research and information gathering are carried out a complete study for the use of new technologies guiding us with the main objective. Recall that rice in Ecuador is part of the most consumed cereal by the population, as it requires higher productivity and efficiency in the quality of their seeds producing large-scale and quality for the needs of the population. The new era in agriculture and the linkage with new technologies have allowed great advances in the improvement of rice cultivation, each of these technological devices have been included with responsibilities and their respective procedures, the way it should be added to the rice field, to facilitate the production and management of the same. The new technologies bring great benefits in the agricultural sector, specifically in rice cultivation, this is demonstrated with an arduous study that is detailed in this document, the same that is supported by the different bibliographic citations used where the use of these modern technologies that now also contribute to the rice sector in the province of Los Rios is evidenced.